Prognostic nomogram incorporating inflammatory cytokines for overall survival in patients with aggressive non-Hodgkin's lymphoma - Zhong, Huijuan (EBioMedicine, 2019)
BACKGROUND: This study aimed to investigate the association of pre-treatment inflammatory status with survival time and to develop a prognostic nomogram incorporating inflammatory cytokines in non-Hodgkin's lymphoma. METHODS: A total of 228 patients with diffuse large B-cell lymphoma (DLBCL) received R-CHOP-based regimens from a prospective randomized study (NCT01852435) were included as a training cohort. Other cohorts of 886 lymphoma patients were served as validation cohorts. Lymphocyte-monocyte ratio (LMR), serum levels of soluble interleukin s(IL)-2R, IL-6, IL-8, IL-10 and tumor necrosis factor-α (TNF-α), were assessed before treatment. Least absolute shrinkage and selection operator (LASSO) regression were used to select variables for nomogram of overall survival (OS). The predictive accuracy of the nomogram was determined by concordance index (C-index). FINDINGS: The nomogram included lactate dehydrogenase (LDH), sIL-2R, TNF-α and decreased LMR. The C-index of the nomogram for OS prediction were range from 0.61 to 0.86 for training cohort of DLBCL and validation cohorts of DLBCL, PTCL, NKTCL and ASCT, which were superior to the predictive power of International Prognostic Index (IPI, 0.67 to 0.84) or NCCN-IPI (0.59 to 0.78), but not in those of indolent lymphoma like FL and MALT. INTERPRETATIONS: The nomogram incorporating inflammatory cytokines provides a useful tool for risk stratification in aggressive non-Hodgkin's lymphomas. FUND: National Natural Science Foundation of China, the Shanghai Commission of Science and Technology, Multicenter Clinical Research Project by Shanghai Jiao Tong University School of Medicine, Clinical Research Plan of SHDC, and Chang Jiang Scholars Program.